Innovative Process Cycle with Zeolite (MS13X) for Post Combustion Adsorption. (July 2017) - Bonalumi, Davide; Lillia, Stefano; Manzolini, Giampaolo; Grande, Carlos
Abstract: This paper reports the integration of Electric swing adsorption (ESA) Process in a Natural Gas Combined Cycle. This process was investigated in the MATESA FP7 project financed by European Commission. The ESA process is modelled through ASPEN Adsorption using both heat and electricity for regenerating the sorbent. The overall heat duty of the sorbent is 4 MJ/kgCO2 where half of this is recovered in the regeneration cycle. The resulting CO2 avoided is around 90% with a net electric efficiency of about 40%. The low efficiency is consequence of the higher energetic value of electricity with respect to the thermal power typically adopted in MEA regeneration. Being the first attempt of simulating this process using multiple heat sources and the recent development of sorbents, significant improvements can be expected by ESA reducing the gap with conventional post-combustion CO2 capture technologies.